Effect Of Cow Products And Botanicals On Management Of Cercospora Leaf Spot Of Fenugreek (Journal of Plant Disease Sciences, 2018)
Cercospora leaf spot incited by Cercospora traversiana reported as the most destructive disease under suitable environmental conditions can cause 80 per cent reduction in yield. Seed treatment and foliar spray of cow urine, cow dung slurry, panchgavya and vanaspativash significantly decreased the percent disease intensity of Cercospora leaf spot. Percent disease intensity was recorded in seed treatment with cow Urine (13.43-33.31), cow dung slurry (13.46-35.24), Panchgavya (14.15-39.33), Vanaspativash (13.96-38.97) and Vanaspativash + cow urine+ cow dung slurry (15.51-40.29) in comparison to control (17.88- 41.34). ). Foliar spray of organic treatment minimized the disease intensity from 20.08 – 21.73% in cow urine, 14.26- 22.22% in cow dung slurry, 15.55 to 22.02% in panchgavya and 14.90 - 19.50% in Vanaspativash over the control. Seed treatments and foliar spray of the organic treatments significantly increased the growth and yield of fenugreek viz. Plant height, primary branching, secondary branching and number of pods per plants and number of grain per pods. The organic treatment induced higher number of grain per pods (5.07 – 17.28%) and test weight of seed (5.46 – 13.72%) that have improve total grain yield of fenugreek (6.67- 42.62%).
Keywords: Cow products; Botanicals; management; Cercospora leaf spot; fenugreek; Trigonella foenum-graecum